Augmented Repair of Massive Rotator cuff tear with Tensor Fascia Lata Autograft. (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the functional outcome of massive rotator cuff tear treated with tensor fascia lata autograft.Methods: This descriptive study was conducted in Hand and Upper limb surgery Center CMH Lahore Medical College Lahore from 23rd December 2016 to 23rd December 2020.All adults patients of either gender and age with massive rotator cuff teat fulfilling the inclusion criteria were operated with tensor fascia lata autograft. Post operative functional outcome was assessed with Shoulder Pain and Disability Index(SPADI). Pre operative and post operative SPADI score was compared and P value was calculated with paired-t test. P value < 0.05 was considered significant.Results: The total number of patients in our study were 10. Mean age was 46.21±8.21 years. Male patients were 8(80%) and female 2(20%).Right shoulder was involved in 7( 70%) patients and left in 3(30%). A significant improvement in SPADI score at 2 years follow up was noted(from 94.34±7% to 19.2±3% with P 0.001).Repeat MRI at 12th week revealed complete cuff healing in 9(90%) patients and partial healing in 1(10%) patient. No retear was noted.Conclusion: Massive rotator cuff tears treated with tensor fascia lata autograft produced complete healing and excellent functional results without any retear. Fascia lata autograft should be the technique of choice for massive irreparable rotator cuff tear.